Evaluation of a third generation anti-HCV assay in predicting viremia in patients with positive HCV antibodies - Silvia Sookoian, MD; Gustavo Castaño, MD (Annals of Hepatology, 2002)
The most practical screening test for hepatitis C virus antibodies are second and third-generation enzyme immunoassays. We evaluated the usefulness of the third generation microparticle enzyme immunoassay (MEIA) in predicting HCV viraemia in anti-HCV positive patients. Serum samples from 106 patients with positive anti-HCV were obtained. To evaluate the diagnostic value of the MEIA test in predicting HCV viraemia, anti-HCV positive patients were categorized in two groups according to the presence or absence of serum HCV-RNA. Among the 106 patients, 26 had non detectable serum HCV-RNA and 80 had detectable HCV-RNA by PCR. The assay automatically calculates a result based on the ratio of sample rate to the cut-of rate for each sample and control (S/CO). When the means of S/CO values for patients with detectable and non detectable HCV-RNA were analyzed, a statistically significant difference was found, (79.3 SD 22.2 vs. 8.2 SD 6.4, respectively) (p 0.0001). We further analyzed the best cut-off value of the S/CO in differentiating viremic from non viremic patients. The S/CO value of 26 showed a sensitivity of 99% and a specificity off 96% in discriminating both categories of HCV infected patients. In conclusion, our data demonstrate that viremic HCV patients had higher S/CO values in the MEIA test in comparison with non viremic patients. Hence, this assay may be used to predict HCV viraemia in anti-HCV positive individuals.